Development of the UK Vessel Health and Preservation (VHP) framework: a multi-organisational collaborative. Issue 2 (March 2016) - Hallam, Carole; Weston, Valya; Denton, Andrea; Hill, Steve; Bodenham, Andrew; Dunn, Helen; Jackson, Tim
Vascular access is an important part of many patient care management plans but has some unwanted risks. Previous work published by Moureau et al. (2012) inspired a working group led by the UK Infection Prevention Society (IPS) to produce a vessel health and preservation (VHP) framework. This was with the intention of producing a resource for frontline staff to be able to assess and select the best vascular access device to meet the individual patient's needs and to preserve veins for future use. The working group produced a framework that used available evidence, expert opinion and some small scale testing of the components of the framework. The work so far has received positive feedback but further work is required to formally evaluate the VHP framework in clinical practice to measure both staff knowledge and patient outcomes.